The bullying, Convention on the Rights of the Child and the school mediation in Argentina - Capomasi, Romina Paola (Avances en Supervisión Educativa, 2014)
Bullying is an hostile conduct or persecution, physical or psychological, carried out by one or several children to the detriment of another. The reasons why a child is chosen as permanent attacks are multiple and depend on each school context. The consequences of this are many: can have problems of integration, can suffer injuries or more serious consequences. Therefore, against the growing aggressiveness among students to question the effectiveness of the guidelines for living together arises the question and need to implement alternative mechanisms for resolution of conflicts which promote habits of peaceful coexistence and contribute to prevent violence in schools, creating spaces pacific of listening dialogue and mutual respect to students who are victims of Bullying are encouraged to ask for help and avoid further damage. This tool also helps stakeholders in the educational community to detect situations of harassment or abuse.